Impulse Buying in Minimarket Retail Consumers: Is it Influenced by Price Discount and Hedonic Shopping Value Mediated by Positive Emotion - SRIYANTO, Agus; VILDAYANTI, Rina Ayu; LESTARI, Khofifa Dwi (PT Keberlanjutan Strategis Indonesia, 2024)
The phenomenon of impulse buying has become an important subject in the study of consumer behavior. With increasing competition in the retail market, a better understanding of the factors that influence impulse buying is essential for retailers to design effective marketing strategies. This issue is important because it provides deeper insight into consumer behavior and offers guidance for retailers in developing more effective marketing approaches. This study aims to identify and analyze the effect of price discounts and hedonic shopping value on impulsive buying and to test the role of positive emotions in mediating the effects of these variables on impulsive buying. The population of this study consisted of retail consumers in minimarkets in Tangerang, Banten, The population is not known for certain. The sample size was 384 respondents. The sample was collected using non-probability sampling techniques, specifically purposive sampling. The data collected were analyzed using Microsoft Excel, Statistical Product and Service Solutions (SPSS), and Partial Least Square (PLS) with path analysis. The results of the study showed that price discounts have a significant impact on impulsive buying. Hedonic shopping value also significantly affects impulsive buying. The indirect effect of price discounts on impulsive buying through positive emotions is not significant. Hedonic shopping value has a significant indirect effect on impulsive buying through positive emotions.